2012
DOI: 10.1007/s10515-011-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Decision support for the software product line domain engineering lifecycle

Abstract: Software product line engineering is a paradigm that advocates the reusability of software engineering assets and the rapid development of new applications for a target domain. These objectives are achieved by capturing the commonalities and variabilities between the applications of the target domain and through the development of comprehensive and variability-covering feature models. The feature models developed within the software product line development process need to cover the relevant features and aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…However, there were mixed opinions regarding the impact of our approach in reducing the time needed to build a product configuration. This is in line with our previous finding regarding a decision support platform for the domain engineering phase [6].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, there were mixed opinions regarding the impact of our approach in reducing the time needed to build a product configuration. This is in line with our previous finding regarding a decision support platform for the domain engineering phase [6].…”
Section: Discussionsupporting
confidence: 93%
“…This was an interesting observation for us given our previous experience. In a related work, we developed a decision support platform for the domain engineering phase of the software product line lifecycle [6]. In our experiments and through the actual tracking of the time taken to perform a domain engineering process with and without the decision support platform, we observed that the time was quite similar for both settings.…”
Section: Lessons Learnedmentioning
confidence: 78%
See 2 more Smart Citations
“…Numerous techniques have been developed to mine variability [10,15,16] and support domain analysis [17,18,19,20,7,6,3,21,22,23], but none of them address the problem of structuring the information in a PCM.…”
Section: Introductionmentioning
confidence: 99%